Exploring Corporate Governance Quality, Audit Remuneration, Company’s performance, Earning management & Financial distress - kai, fan (2011)
This study investigates that how audit fees and non-audit services fees might be influenced by the quality (i.e. effectiveness) of CG. It explores corporate governance (CG) quality by taking the research forward to explore the influence of corporate governance quality on firstly audit and non-audit pricings and then the effects of these two variables on company performance, the practice of earning management and financial distress. Regression models are used to first explain the association between audit remunerations (AF & NASF) and audit committee effectiveness (ACE) and then explain the interactive effects of these two factors (AF+ACE & NASF+ACE) on company performance (ROA), earning management (ER) and financial distress (FD).